MORPHOLOGICAL DESCRIPTION OF INTERNAL ORGAN COLOR AND ITS RELATIONSHIP TO BODY WEIGHT OF FREE-RANGE CHICKENS IN THE PALEMBANG LANDFILL ENVIRONMENT - Mutia Nurrahmandani; Sofia Sandi; Asep Indra Munawar Ali (BIOVALENTIA: Biological Research Journal, 2022)
The landfill environment in Palembang City produces various types of waste so that people keep free-range chickens around the environment, which is potentially harmful to livestock health. This study aims to determine the color morphology of the internal organs (liver and heart) and the relationship between body weight and organ weight. The number of free-range chickens used was 30, with one year. The morphological description of organ color was carried out by direct observation, and sampling was carried out by weighing free-range chickens body weight and organ weight. This study used the Pearson correlation statistical test, and secondary data was collected on waste data in the landfill environment. The results showed that the relationship between body weight and liver weight was 0.694, and the correlation value between body weight and heart weight was 0.663 in native chickens in the landfill environment. The results of the two values have a strong correlation interpretation, which means that when the chicken's body weight increases, the weight of the liver and heart of the chicken will also increase. The liver is faded red with normal size in native chickens in the landfill environment in the morphological picture. While the color of the heart is red, and the size is normal.